Deducing the Fatigue Crack Growth Rates of Natural Flaws in Silicon Nitride Ceramics: Role of R‐Curves. Issue 8 (21st May 2013) - Härtelt, Martin; Fünfschilling, Stefan; Schwind, Thomas; Riesch‐Oppermann, Heinz; Fett, Theo; Kruzic, Jamie J.; Marshall, D. B.
<x xml:space="preserve">Abstract</x> Fatigue failure is a concern when high‐strength, high‐toughness silicon nitride ceramics are used in mechanical components and the growth of natural flaws will determine the usable upper bound strength. In this study a fracture resistance curve (R‐curve) model is incorporated into an established method for deducing natural flaw growth rates from a combination of strength and fatigue life data for smooth specimens. Experimental data for a commercial silicon nitride, SL200, were examined. When compared with results deduced using a constant fracture toughness model, the new method gives more physically realistic growth rate results. Specifically, by incorporating the R‐curve the deduced fatigue threshold is equal to the reported intrinsic toughness for crack propagation of 2.2 MPa√m, whereas the constant fracture toughness model gives a physically unrealistic threshold value. Furthermore, much better agreement is achieved with the growth rates measured using macroscopic compact‐tension specimens. Overall, it is concluded that the R‐curve effect should not be ignored when deducing the fatigue crack growth rates of natural flaws in high‐toughness silicon nitride ceramics.